Association of Menstrual Extension and Surgery Effectiveness with Ultrasound Parameters of Cesarean Section Scar Diverticulum in Patients Undergoing Transvaginal Uterine Diverticulum Repair - Qing Yang; Min Ren; Xiaoli Lv; Fenghua Chen (Hindawi Limited, 2019)
The association of residual myometrium thickness (RMT) and scar defect depth (D) with menstrual abnormalities and the effectiveness of vaginal repair remain to be determined in patients with cesarean section scar diverticulum (CSD). To assess the value of ultrasound to predict vaginal repair effectiveness. This was a retrospective study of patients with CSD treated with vaginal repair between 01/2014 and 02/2016 at Shanghai First Maternity and Infant Hospital (Tongji University). Transvaginal ultrasound was performed before and 3 months after surgical repair. RMT, D, scar defect length (L), and scar defect width (W) were measured. Width (W), D, and L increased along the duration of menstrual period (P<0.05). When the menstrual extension time was ≥15 days, RMT/D and RMT/RMT+D were smaller than in patients with period <15 days (P<0.05). L was the most positively correlated ultrasonic parameter with menstrual prolongation (r=0.492). RMT/D and RMT/RMT+D were negatively correlated with prolonged menstruation (r=‐0.304 and -0.305, respectively). RMT/D and RMT/RMT+D were associated with the disappearance of CSD after vaginal repair (P<0.05). The cutoff value of RMT/RMT+D was 0.496, with sensitivity of 53.0% and specificity of 61.4%. L of CSD is closely correlated with menstrual extension but has no relationship with the effectiveness of surgery. RMT/RMT+D is correlated with menstrual extension time ≥15 days and the effectiveness of vaginal repair.